Montagu : urban conservation in a small town : the role of voluntary conservation groups and planning law in heritage resource management - Vermeulen, Frederik Saaiman (Division of Geomatics, 2015)
Conservation in Montagu started in the early 1970s, with the rescuing and restoration of significant buildings and the declaration of 21 National Monuments (now called Provincial Heritage Sites), which safeguarded those buildings when no other heritage protections were in place. This was followed by a conservation study by Todeschini and Japha in 1990, identifying heritage resources, delineating conservation areas and providing guidelines. This case study has found that, with a few exceptions, the conservation endeavours in Montagu during the past 40 years have been successful.